Pencegahan Judi Online di Kalangan Masyarakat Melalui Program Sosialiasi Terpadu - Srirejeki, Kiky; Khairurrizqo, Khairurrizqo (Jurnal Pengabdian Bisnis dan Akuntansi, 2025)
Online gambling has become a growing social issue in Indonesian society, particularly among youth and vulnerable groups. This community service initiative aims to prevent online gambling addiction through a comprehensive outreach program conducted in collaboration with local community organizations in Purbalingga Regency. The implementation methodology includes interactive educational sessions, awareness campaigns, and community-based prevention programs. The program focuses on three main pillars: education on the dangers of online gambling, strengthening community resilience, and promoting healthy alternative activities. Expected outcomes include increased public awareness of the risks of online gambling, enhanced community capacity to identify and prevent gambling addiction, and strengthened social support networks. It is anticipated that this initiative will make a significant contribution to reducing online gambling activities and encouraging healthier lifestyle choices within the